Voluntary Movement Takes Shape: The Link Between Movement Focusing and Sensory Input Gating - Belvisi, Daniele; Conte, Antonella; Cortese, Francesca Natalia; Tartaglia, Matteo; Manzo, Nicoletta; Li Voti, Pietro; Suppa, Antonio; Berardelli, Alfredo (Frontiers in Human Neuroscience, 2018)
The aim of the study was to investigate the relationship between motor surround inhibition (mSI) and the modulation of somatosensory temporal discrimination threshold (STDT) induced by voluntary movement. Seventeen healthy volunteers participated in the study. To assess mSI, we delivered transcranial magnetic stimulation single pulses to record motor evoked potentials from the right abductor digiti minimi (ADM) (“surround muscle”) during brief right little finger flexion. mSI was expressed as the ratio of ADM motor evoked potential amplitude during movement to motor evoked potential amplitude at rest. We preliminarily measured STDT values by assessing the shortest interval at which subjects were able to recognize a pair of electric stimuli, delivered over the volar surface of the right little finger, as separate in time. We then evaluated the STDT by using the same motor task used for mSI. mSI and STDT modulation were evaluated at the same time points during movement. mSI and STDT modulation displayed similar time-dependent changes during index finger movement. In both cases, the modulation was maximally present at the onset of the movement and gradually vanished over about 200 ms. Our study provides the first neurophysiological evidence about the relationship between mSI and tactile-motor integration during movement execution.